2015
DOI: 10.1099/jmmcr.0.000079
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of seven patients with chronic mastoiditis

Abstract: Introduction: Chronic mastoiditis is generally a result of chronic suppurative otitis media; it is rarely a result of failure of treatment of acute mastoiditis. Case presentation: Seven patients with chronic mastoiditis were investigated. Four patients had bilateral mastoiditis. The duration of illness ranged from 1 to 45 years. A comparison between operative and external auditory canal cultures was performed. The operative specimens were obtained directly from the infected mastoids. The external ear and masto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[9][10][11] In yet another study by Mousa, Pseudomonas was the most common organism isolated (23.5% of cases) followed by, which was followed by Proteus spp, coagulase-negative Staphylococci, and Prevotela melaninogenica. 12 The high prevalence was attributed to the improper use of antibiotic ear drops that transmit this organism from skin into middle ear and mastoid. Moreover, Pseudomonas was resistant to most of the antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] In yet another study by Mousa, Pseudomonas was the most common organism isolated (23.5% of cases) followed by, which was followed by Proteus spp, coagulase-negative Staphylococci, and Prevotela melaninogenica. 12 The high prevalence was attributed to the improper use of antibiotic ear drops that transmit this organism from skin into middle ear and mastoid. Moreover, Pseudomonas was resistant to most of the antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Pseudomonas was resistant to most of the antibiotics. 12 A study by Verhoeff et al reported the most common organism to cause CSOM was Pseudomonas and this organism was particularly implicated in in the causation of bony necrosis and mucosal disease. 13 Another study involving CSOM also considers Pseudomonas to me the most common causative organism.…”
Section: Discussionmentioning
confidence: 99%